1991
DOI: 10.1128/mcb.11.6.2980
|View full text |Cite
|
Sign up to set email alerts
|

The yeast SLY gene products, suppressors of defects in the essential GTP-binding Ypt1 protein, may act in endoplasmic reticulum-to-Golgi transport.

Abstract: It has been shown previously that defects in the essential GTP-binding protein, Yptlp, lead to a block in protein transport from the endoplasmic reticulum (ER) to the Golgi apparatus in the yeast Saccharomyces cerevisiae. Here we report that four newly discovered suppressors of YPTI deletion (SLYI-20, SLY2, SLY12, and SLY41) to a varying degree restore ER-to-Golgi transport defects in cells lacking Yptlp. These suppressors also partially complement the sec21-1 and sec22-3 mutants which lead to a defect early i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
161
0
3

Year Published

1992
1992
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(167 citation statements)
references
References 59 publications
(67 reference statements)
3
161
0
3
Order By: Relevance
“…Both Sec22p and Sed5p show strong genetic interactions with genes encoding proteins involved in Golgi-ER retrograde transport (37,69,70). Double mutant analysis revealed that the same is true for dsl1-22.…”
Section: Dsl1p Is Required For Golgi 3 Er Traffickingmentioning
confidence: 75%
See 1 more Smart Citation
“…Both Sec22p and Sed5p show strong genetic interactions with genes encoding proteins involved in Golgi-ER retrograde transport (37,69,70). Double mutant analysis revealed that the same is true for dsl1-22.…”
Section: Dsl1p Is Required For Golgi 3 Er Traffickingmentioning
confidence: 75%
“…The mutants identified were accordingly named dsl1-1 to dsl1-7 (dependent on SLY1-20). SLY1-20 is a dominant mutation, which suppresses the defects in several yeast mutants affected in ER-to-Golgi transport (27,37,(57)(58)(59)(60). Accordingly, the mutant we obtained was renamed dsl1-22.…”
Section: Dsl1p Is Required For Golgi 3 Er Traffickingmentioning
confidence: 99%
“…Several v-SNAREs with functions in traffic from the ER to the Golgi apparatus or in retrograde traffic within the Golgi apparatus have been identified in yeast: Sec22p/Sly2p, Bet1p/Sly12p, Bos1p, Sft1p, Ykt6p, and Gos1p (Newman et al, 1990;Ossig et al, 1991;McNew et al, 1997;Holthuis et al, 1998a). The v-SNAREs Snc1p and Snc2p interact with Sso1p and Sso2p in secretion (Protopopov et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Yeast S. cerevisiae possesses four Sec1p-family proteins: Sec1p mediates vesicle fusion at the plasma membrane (Novick et al, 1981;Carr et al, 1999), Sly1p mediates vesicle fusion at the endoplasmic reticulum-Golgi interface (Ossig et al, 1991), Vps33p is required for endosome to vacuole transport and vacuole maintenance (Banta et al, 1990), and Vps45p mediates Golgi-to-vacuole transport (Piper et al, 1994;Cowles et al, 1994). Sec1p is the closest homologue of the mammalian Munc18-1 that has been shown to associate with syntaxin 1 and to regulate the syntaxin 1-synaptobrevin-SNAP-25 SNARE complex assembly (Misura et al, 2000;Kauppi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%